Longitudinal cortical thinning and cognitive decline in patients with early‐ versus late‐stage subcortical vascular mild cognitive impairment. (21st December 2017) - Lee, J.; Seo, S. W.; Yang, J.‐J.; Jang, Y. K.; Lee, J. S.; Kim, Y. J.; Chin, J.; Lee, J. M.; Kim, S. T.; Lee, K.‐H.; Lee, J. H.; Kim, J. S.; et al.
Abstract : Background and purpose: Biomarker changes in cognitively impaired patients with small vessel disease are largely unknown. The rate of amyloid/lacune progression, cortical thinning and cognitive decline were evaluated in subcortical vascular mild cognitive impairment (svMCI) patients. Methods: Seventy‐two svMCI patients were divided into early stage (ES‐svMCI, n = 39) and late stage (LS‐svMCI, n = 33) according to their Clinical Dementia Rating Sum of Boxes score. Patients were annually followed up with neuropsychological tests and brain magnetic resonance imaging for 3 years, and underwent a second [ 11 C] Pittsburgh compound B (PiB) positron emission tomography scan within a mean interval of 32.4 months. Results: There was no difference in the rate of increase in PiB uptake or lacune number between the ES‐svMCI and LS‐svMCI. However, LS‐svMCI showed more rapid cortical thinning and cognitive decline than did the ES‐svMCI. Conclusions: We suggest that, whilst the rate of change in pathological burden did not differ between ES‐svMCI and LS‐svMCI, cortical thinning and cognitive decline progressed more rapidly in the LS‐svMCI.